Perovskite thin film and preparation method and application thereof
By doping small molecules of diethyl sulfate into the perovskite precursor solution, combining it with PbI2, delaying the crystallization of perovskite films, the problem of difficulty in preparing high-quality perovskite films in the prior art is solved, and an efficient, stable and simplified film preparation process is achieved.
Patent Information
- Application Number
- CN202510190643.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The prior art is difficult to effectively prepare high-quality perovskite films, especially in improving the long-term stability of the film and the photoelectric conversion efficiency.
By doping small molecules of diethyl sulfate into the perovskite precursor solution, it combines with PbI2, delaying the crystallization of perovskite films, and achieving the preparation of large-grain high-quality perovskite films.
This method not only improves the stability of the perovskite layer and the efficiency and stability of solar cell devices, but also simplifies the preparation process, reduces costs, and gives the film a wider application potential.
Smart Images

Figure CN119894336A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite film and a preparation method and application thereof. Background Art
[0002] As photovoltaic technology continues to make breakthroughs, metal halide perovskite solar cells are creating an unprecedented revolution in the photovoltaic field with their excellent photoelectric conversion efficiency, excellent light capture characteristics and relatively low preparation costs. The core of this technology lies in the perovskite thin film light absorption layer, which has a unique ABX 3 The crystal structure (where the A position is usually occupied by an alkali metal ion or an organic cation, the B position is a transition metal ion, and the X position is a halogen ion) gives perovskite materials excellent photoelectric properties. In recent years, the photoelectric conversion efficiency of perovskite solar cells under laboratory conditions has significantly surpassed that of traditional thin-film solar cells. This milestone achievement indicates that perovskite technology is gradually becoming the core force of the photovoltaic industry and leading the future development of photovoltaic technology.
[0003] Although the photoelectric conversion efficiency of perovskite solar cells has increased by leaps and bounds, its long-term stability remains a major challenge in the current research field. The core light-absorbing layer perovskite will degrade when exposed to external factors such as light, heat, water vapor, and oxygen during device operation. These degradations often start from the defects of the perovskite film and trigger a chain reaction, resulting in the deterioration of the quality of the perovskite film, the reduction of carrier extraction and transmission efficiency, and further leading to the efficiency attenuation of the perovskite solar cell. Therefore, how to prepare high-quality perovskite films is crucial to improving the long-term stability of solar cells.
[0004] The defects of perovskite films are mainly divided into intrinsic defects and extrinsic defects. Intrinsic defects are defects caused by the structural characteristics of perovskite films during their formation. These defects mainly include: point defects: caused by the absence of A-site ions, B-site ions and oxygen ions. In perovskite films, the absence or replacement of ions may lead to incomplete lattice structure, thus forming point defects. Domain wall: The domain wall formed between domains of different orientations is also one of the common intrinsic defects in perovskite films. Extrinsic defects are defects induced by external factors. These defects include: during the crystallization process of the film, if the lattice arrangement is not perfect or the atomic period is disturbed, it may lead to the formation of high-density defects; during the preparation and subsequent treatment of perovskite films, if they come into contact with the external environment (such as water, light, oxygen, etc.), degradation reactions may occur, causing the crystal to deform, stretch, twist, etc., and then form defects. The most effective means to regulate and passivate defects in perovskite films is to in-situ regulate defects in the film bulk.
[0005] An existing method for preparing high-quality perovskite films is to introduce small molecules at the buried interface for modification to provide a better template for perovskite growth. However, this method often requires the introduction of additional operating steps during the preparation process, which is not conducive to commercial production.
[0006] Another existing method for preparing high-quality perovskite films is to introduce some small molecules of organic ammonium salts with long carbon chains on the surface of the perovskite for post-treatment, thereby passivating the surface defects of the perovskite film. On the one hand, this method introduces additional operating steps, which is not conducive to commercial production; on the other hand, the post-treatment is performed after the perovskite film has completed crystallization, and the passivation of defects in the bulk phase of the perovskite film is quite limited, making it difficult to effectively improve the crystallization quality of the perovskite film. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a perovskite film and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art, by doping small molecules into the perovskite precursor solution so that the small molecules preferentially react with PbI in the precursor solution. 2 The combination delays the crystallization of perovskite films and realizes the preparation of large-grained high-quality perovskite films, which not only improves the stability of the perovskite layer, but also improves the efficiency and stability of solar cell devices. It is used to solve the technical problems that the existing high-quality preparation methods of the light-absorbing layer in perovskite solar cell devices are difficult to adapt to different preparation methods, and the commonly used passivation strategies often require the introduction of additional operating steps, making it difficult to achieve effective passivation of the bulk defects of the perovskite film.
[0008] The present invention adopts the following technical solutions: A method for preparing a perovskite film comprises dissolving a diethyl sulfate small molecule in a perovskite precursor solution, wherein the concentration of the diethyl sulfate small molecule in the perovskite precursor solution is 3-15 mg / mL, then coating the perovskite precursor solution containing the small molecule on a substrate, and obtaining the perovskite film after annealing.
[0009] Preferably, the diethyl sulfate small molecule is diethyl sulfate, and the molecular structure is C 4 H 10 O 4 S.
[0010] Preferably, the annealing temperature is 50-150° C., and the annealing time is 5-20 mins.
[0011] Preferably, the perovskite material used in the perovskite precursor solution includes formamidine hydroiodide, cesium iodide, lead iodide and lead bromide.
[0012] Preferably, the perovskite precursor solution containing small molecules is coated on the substrate by spin coating, spray coating, immersion coating or scraping coating.
[0013] Another technical solution of the present invention is a perovskite film.
[0014] Another technical solution of the present invention is a solar cell device, comprising a substrate, a transparent electrode, an electron transport layer, a perovskite film layer, a hole transport layer and a top electrode stacked in sequence from bottom to top; the perovskite film is prepared according to the method, and the thickness of the perovskite film layer is 300~600 nm.
[0015] Preferably, the transparent electrode is made of inorganic material or organic conductive polymer, the inorganic material is a metal oxide selected from indium tin oxide, zinc oxide or tin oxide, or a metal selected from gold, copper, silver or zinc; the organic conductive polymer is polythiophene, polyethylene sodium benzene sulfonate or polyaniline.
[0016] Preferably, the electron transport layer is made of tin oxide, titanium oxide, zinc oxide, fullerene or a fullerene derivative.
[0017] Preferably, the hole transport layer is made of nickel oxide, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly-3-hexylthiophene or poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].
[0018] Compared with the prior art, the present invention has at least the following beneficial effects: A method for preparing a perovskite film, wherein the diethyl sulfate small molecule can form a relatively strong network structure in the perovskite precursor solution during the annealing process. This network structure helps to enhance the mechanical strength and flexibility of the perovskite film, especially when the film is used in flexible electronic devices (such as flexible solar cells), it has important advantages; by controlling the concentration of the diethyl sulfate small molecule (3~15 mg / mL), the surface structure and interface properties of the film can be regulated, thereby affecting the photoelectric properties of the perovskite material. For example, an appropriate amount of small molecules may help to increase the carrier transfer rate or reduce the interface defect density, thereby improving the photoelectric conversion efficiency of the perovskite solar cell; the process of adding diethyl sulfate small molecules to the perovskite precursor solution and forming a perovskite film by coating and annealing can simplify the traditional perovskite film preparation method. This method may reduce the dependence on complex additives or external equipment, while improving the quality of the film by optimizing the solution composition and process conditions; the present invention not only improves the mechanical strength, chemical stability, and photoelectric properties of the perovskite film by introducing the small molecule diethyl sulfate, but also simplifies the preparation process and gives the film a wider range of application potential. These advantages help to improve the application of perovskite materials in optoelectronics, electronics, and other fields Furthermore, by introducing the small molecule diethyl sulfate into the perovskite precursor solution, the mechanical strength, chemical stability, charge transfer performance and photoelectric conversion efficiency of the perovskite film can be improved, while simplifying the preparation process, reducing costs, and giving the film more controllable functions.
[0019] Furthermore, the perovskite material is formamidine hydroiodide, cesium iodide, lead iodide or lead bromide, which can form an efficient perovskite structure, provide high photoelectric conversion efficiency, and improve the environmental stability of perovskite solar cells, especially in high humidity and high temperature environments, slowing down the degradation of the perovskite layer.
[0020] A perovskite film with excellent light absorption properties, capable of effectively absorbing visible light. The band gap of the perovskite material is adjusted through different formulas so that the film can exhibit optimal light absorption under different lighting conditions, thereby optimizing the photoelectric performance. It does not require the use of highly toxic solvents or complex high-temperature treatments and is relatively more environmentally friendly.
[0021] A solar cell device, the perovskite film can provide appropriate light transmittance and reflectivity, help reduce interface defects and carrier recombination losses, thereby improving the overall performance and stability of the solar cell, and has the advantages of high photoelectric conversion efficiency, good stability, long service life, low-cost production and wide application potential.
[0022] In summary, the method of the present invention can significantly increase the grain size of the perovskite film, improve the crystallization quality of the perovskite film, has a simple process, low equipment requirements, high stability and repetition rate, low dependence on the environment, and low cost.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings to be used in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 Schematic diagram of perovskite solar device; Figure 2 The scanning electron microscope images of Example 1 before and after doping with small molecules; Figure 3 The voltage-current density curves of the devices prepared by the modified and unmodified perovskite layers in Example 1; Figure 4The scanning electron microscope images of Example 2 before and after doping with small molecules; Figure 5 The voltage-current density curves of the devices prepared by the modified and unmodified perovskite layers in Example 2; Figure 6 The scanning electron microscope images of Example 3 before and after doping with small molecules; Figure 7 The voltage-current density curves of the devices prepared by the modified and unmodified perovskite layers in Example 3; Figure 8 The scanning electron microscope images before and after doping with small molecules; Fig. 9 A comparison of the voltage-current density curves of devices prepared with modified and unmodified perovskite layers.
[0026] Among them, 1. substrate; 2. transparent electrode; 3. electron transport layer; 4. perovskite thin film layer; 5. hole transport layer; 6. top electrode. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0029] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0030] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0031] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0032] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" represents that all real numbers between "6-22" are listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0033] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0034] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0035] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0036] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0037] The present invention provides a perovskite film and a preparation method and application thereof, wherein small molecules are dissolved in a perovskite precursor solution at a certain concentration, the growth of the perovskite film is effectively delayed, the crystallization quality of the perovskite film is improved, the perovskite grains are enlarged, and the vacancy defects in the film are passivated; at the same time, the photoelectric performance and stability of a battery device based on the doped film are significantly improved; the present invention realizes the preparation of a high-quality perovskite film by doping specific small molecules into the perovskite precursor solution, improves the device operation stability from the inside of the device, and is conducive to the further development of perovskite solar cells.
[0038] The present invention provides a method for preparing a perovskite film, comprising the following steps: The diethyl sulfate small molecule is dissolved in the perovskite precursor solution, and the concentration of the diethyl sulfate small molecule is selected to be 3~15 mg / mL; then the perovskite precursor solution containing the small molecule is coated on a substrate, and then annealed at 50~150 ℃ for 5~20 mins to obtain a high-quality perovskite film, delay the crystallization of the perovskite film, improve the crystallization quality of the perovskite film, and improve the photoelectric performance and stability of the perovskite solar cell device.
[0039] Diethyl sulfate small molecule uses diethyl sulfate, the molecular structure is C 4 H 10 O 4 S.
[0040] The perovskite material is formamidine hydroiodide, cesium iodide, lead iodide or lead bromide.
[0041] The perovskite precursor solution containing small molecules is coated on the substrate by spin coating, spray coating, immersion coating and scraping coating. The substrate includes a substrate, a substrate plus a transparent electrode, and a substrate plus a transparent electrode plus a transmission layer.
[0042] See also Figure 2 The present invention provides a solar cell device, comprising a substrate 1, a transparent electrode 2, an electron transport layer 3, a perovskite film layer 4, a hole transport layer 5 and a top electrode 6 which are stacked in sequence; wherein the thickness of the perovskite film layer 4 is 300-600 nm.
[0043] The substrate 1 is made of glass or a flexible substrate, and the flexible substrate is made of polyester or polyimide compounds.
[0044] The transparent electrode 2 is made of inorganic material or organic conductive polymer. The inorganic material is indium tin oxide, zinc oxide or a metal oxide of tin oxide or a metal of gold, copper, silver or zinc. The organic conductive polymer is polythiophene, polyethylene sodium benzene sulfonate or polyaniline.
[0045] The material of the electron transport layer 3 is tin oxide, titanium oxide, zinc oxide, fullerene or a fullerene derivative.
[0046] The material of the hole transport layer 5 is nickel oxide, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD for short), poly-3-hexylthiophene (P3HT for short) or poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA for short).
[0047] The material of the top electrode 6 is metal, and the metal is gold, silver, copper or aluminum.
[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] Example 1 See also Figure 1 The perovskite solar device according to the first embodiment of the present invention has the following structure: Glass (plastic) substrate / ITO (100 nm) / NiOx (30nm) / FA 0.8 Cs 0.2 Pb(I 0.65 Br 0.35 )3 (350 nm) / C 60 (20 nm) / Ag(120 nm).
[0050] (1) Cleaning of the glass substrate pre-engraved with ITO: The transparent conductive substrate 1 (ITO glass) is cleaned by ultrasonic method using ethanol, acetone and deionized water, and then placed under an infrared lamp for drying. The ITO film on the transparent conductive substrate 1 is used as the top electrode layer 2 of the device. The square resistance of the ITO film is 15Ω to 30Ω, and the film thickness is 80 to 120nm. (2) Preparation of hole transport layer: The dried substrate was treated with UV-ozone for 5-10 minutes, then placed on a coater and the prepared NiOx aqueous solution was spin-coated into a film using a static batching method. The coater speed was 3000 rpm and the coater time was controlled at 45 s. The sample was dried at 150 °C for 20 mins and the thickness was 30 nm. (3) Preparation of perovskite layer: Weigh 328.46 mg of PbI 2 , 289.01 mg of PbBr 2 , 206.40 mg FAI, 77.9 mg CsI The above materials were added to a mixed solution of 0.75 mL DMF and 0.25 mL DMSO to form a precursor solution. 3 mg C 4 H 10 O 4 S was added to the precursor solution and stirred overnight. After filtration, it was spin-coated on the electron transport layer at 4000 rpm for 60 s; and 0.5 mL of chlorobenzene was added to the top of the solution at 25 s. After spin coating, the substrate was annealed on a drying table at 80°C for 5 mins. The film thickness was 350 nm. Figure 2 This is a scanning electron microscope image before and after doping with small molecules. It can be seen that the grain size of the perovskite film is significantly increased after doping. (4) Preparation of electron transport layer: The spin-coated and dried substrate is placed in a vacuum chamber and evaporated C 60 , the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 20 nm; (5) Preparation of the top electrode: The spin-coated and dried substrate is placed in a vacuum chamber and metallic silver is evaporated. The evaporation rate of the material film is 0.1 nm / s and the film thickness is 120 nm.
[0051] Figure 3The voltage-current density curves of devices prepared with modified and unmodified perovskite layers are compared. It can be seen from the figure that the device performance of the device prepared with the treated perovskite layer has been greatly improved: the fill factor has increased from 62% to 65%, and the energy conversion efficiency has increased from 14.65% to 15.52%.
[0052] Example 2 See also Figure 1 The perovskite solar device according to the first embodiment of the present invention has the following structure: Glass (plastic) substrate / ITO (100 nm) / NiOx (30nm) / FA 0.8 Cs 0.2 Pb(I 0.65 Br 0.35 ) 3 (350nm) / C 60 (20 nm) / Ag(120 nm).
[0053] (1) Cleaning of the glass substrate pre-engraved with ITO: The transparent conductive substrate 1 (ITO glass) is cleaned by ultrasonic treatment with ethanol, acetone, and deionized water, and then placed under an infrared lamp for drying. The ITO film on the transparent conductive substrate 1 is used as the top electrode layer 2 of the device. The square resistance of the ITO film is 15Ω to 30Ω, and the film thickness is 80 to 120nm. (2) Preparation of hole transport layer: The dried substrate was treated with UV-ozone for 5-10 minutes, then placed on a coater and the prepared NiOx aqueous solution was spin-coated into a film using a static batching method. The coater speed was 3000 rpm and the coater time was controlled at 45 s. The sample was dried at 150 °C for 20 mins and the thickness was 30 nm. (3) Preparation of perovskite layer: Weigh 328.46 mg of PbI 2 , 289.01 mg of PbBr 2 , 206.40 mg FAI, 77.9 mg CsI The above materials were added to a mixed solution of 0.75 mL DMF and 0.25 mL DMSO to form a precursor solution. 8 mg C 4 H 10 O 4 S was added to the precursor solution and stirred overnight. After filtration, it was spin-coated onto the electron transport layer at 4000 rpm for 60 s; and 0.5 mL of chlorobenzene was added to the solution at 25 s. After spin coating, the substrate was annealed at 100 °C for 10 mins. The film thickness was 350 nm. Figure 4This is a scanning electron microscope image before and after doping with small molecules. It can be seen that the grain size of the perovskite film is significantly increased after doping.
[0054] (4) Preparation of electron transport layer: Place the spin-coated and dried substrate into a vacuum chamber and evaporate C 60 , the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 20 nm; (5) Preparation of the top electrode: Place the spin-coated and dried substrate into a vacuum chamber and evaporate metallic silver. The evaporation rate of the material film is 0.1 nm / s and the film thickness is 120 nm.
[0055] Figure 5 The voltage-current density curves of devices prepared with modified and unmodified perovskite layers are compared. It can be seen from the figure that the device performance of the device prepared with the treated perovskite layer has been greatly improved: the fill factor has increased from 62% to 70%, and the energy conversion efficiency has increased from 14.65% to 18.59%.
[0056] Example 3 See also Figure 1 The perovskite solar device according to the first embodiment of the present invention has the following structure: Glass (plastic) substrate / ITO (100 nm) / NiOx (30nm) / FA 0.8 Cs 0.2 Pb(I 0.65 Br 0.35 ) 3 (350 nm) / C 60 (20 nm) / Ag(120 nm).
[0057] (1) Cleaning of the glass substrate pre-engraved with ITO: The transparent conductive substrate 1 (ITO glass) is cleaned by ultrasonic method using ethanol, acetone and deionized water, and then placed under an infrared lamp for drying. The ITO film on the transparent conductive substrate 1 is used as the top electrode layer 2 of the device. The square resistance of the ITO film is 15Ω to 30Ω, and the film thickness is 80 to 120nm. (2) Preparation of hole transport layer: The dried substrate was treated with UV-ozone for 5-10 minutes, then placed on a coater and the prepared NiOx aqueous solution was spin-coated into a film using a static batching method. The coater speed was 3000 rpm and the coater time was controlled at 45 s. The sample was dried at 150 °C for 20 mins and the thickness was 30 nm. (3) Preparation of perovskite layer: Weigh 328.46 mg of PbI 2 , 289.01 mg of PbBr2 , 206.40 mg FAI, 77.9 mg CsI The above materials were added to a mixed solution of 0.75 mL DMF and 0.25 mL DMSO to form a precursor solution. 12 mg C 4 H 10 O 4 S was added to the precursor solution and stirred overnight. After filtration, it was spin-coated onto the electron transport layer at 4000 rpm for 60 s; and 0.5 mL of chlorobenzene was added to the top of the solution at 25 s. After spin coating, the substrate was annealed at 100 °C for 15 mins. The film thickness was 350 nm. Figure 6 This is a scanning electron microscope image before and after doping with small molecules. It can be seen that the grain size of the perovskite film is significantly increased after doping.
[0058] (4) Preparation of electron transport layer: Place the spin-coated and dried substrate into a vacuum chamber and evaporate C 60 , the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 20 nm; (5) Preparation of the top electrode: Place the spin-coated and dried substrate into a vacuum chamber and evaporate metallic silver. The evaporation rate of the material film is 0.1 nm / s and the film thickness is 120 nm.
[0059] Figure 7 The voltage-current density curves of devices prepared with modified and unmodified perovskite layers are compared. It can be seen from the figure that the device performance of the device prepared with the treated perovskite layer has been greatly improved: the fill factor has increased from 62% to 65%, and the energy conversion efficiency has increased from 14.65% to 15.55%.
[0060] Example 4 See also Figure 1 The perovskite solar device according to the first embodiment of the present invention has the following structure: Glass (plastic) substrate / ITO (100 nm) / NiOx (30nm) / FA 0.8 Cs 0.2 Pb(I 0.65 Br 0.35 ) 3 (350 nm) / C 60 (20 nm) / Ag(120 nm).
[0061] (1) Cleaning of the glass substrate pre-engraved with ITO: The transparent conductive substrate 1 (ITO glass) is cleaned by ultrasonic method using ethanol, acetone and deionized water, and then placed under an infrared lamp for drying. The ITO film on the transparent conductive substrate 1 is used as the anode layer 2 of the device. The square resistance of the ITO film is 15Ω to 30Ω, and the film thickness is 80 to 120nm. (2) Preparation of hole transport layer: The dried substrate was treated with UV-ozone for 5-10 minutes, then placed on a coater and the prepared NiOx aqueous solution was spin-coated into a film using a static batching method. The coater speed was 3000 rpm and the coater time was controlled at 45 s. The sample was dried at 150 °C for 20 mins and the thickness was 30 nm. (3) Preparation of perovskite layer: Weigh 328.46 mg of PbI 2 , 289.01 mg of PbBr 2 , 206.40 mg FAI, 77.9 mg CsI The above materials were added to a mixed solution of 0.75 mL DMF and 0.25 mL DMSO to form a precursor solution. 15 mg C 4 H 10 O 4 S was added to the precursor solution and stirred overnight. After filtration, it was spin-coated on the electron transport layer at 4000 rpm for 60 s; and 0.5 mL of chlorobenzene was added to the solution at 25 s. After spin coating, the substrate was annealed on a 100°C drying table for 15 mins. The film thickness was 350 nm. Figure 8 This is a scanning electron microscope image before and after doping with small molecules. It can be seen that the grain size of the perovskite film is significantly increased after doping. (4) Preparation of electron transport layer: The spin-coated and dried substrate is placed in a vacuum chamber and evaporated C 60 , the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 20 nm; (5) Preparation of anode: The spin-coated and dried substrate was placed in a vacuum chamber and metallic silver was evaporated. The evaporation rate of the material film was 0.1 nm / s and the film thickness was 120 nm.
[0062] Fig. 9 The voltage-current density curves of devices prepared with modified and unmodified perovskite layers are compared. It can be seen from the figure that the device performance of the device prepared with the treated perovskite layer has been greatly improved: the fill factor has increased from 60% to 65%, and the energy conversion efficiency has increased from 14.57% to 15.58%.
[0063] In summary, the perovskite film and its preparation method and application of the present invention passivate the vacancy defects of the perovskite film while improving the crystallization quality of the perovskite film. The preparation method can be adapted to various preparation methods, including but not limited to large-area preparation methods such as spin coating, scraper coating, and spray coating, and will not introduce additional preparation processes, thereby ensuring the repeatability and low cost of high-quality preparation.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a perovskite film, characterized in that: The diethyl sulfate small molecule is dissolved in the perovskite precursor solution, and the concentration of the diethyl sulfate small molecule in the perovskite precursor solution is 3~15 mg / mL. The perovskite precursor solution containing the small molecule is then coated on a substrate, and a perovskite film is obtained after annealing.
2. The method for preparing a perovskite thin film according to claim 1, characterized in that: The small molecule uses diethyl sulfate, and the molecular structure is C4H 10 O4S.
3. The method for preparing a perovskite thin film according to claim 1, characterized in that: The annealing temperature is 50~150℃, and the annealing time is 5~20 mins.
4. The method for preparing a perovskite thin film according to claim 1, characterized in that: The perovskite materials used in the perovskite precursor solution include formamidine hydroiodide, cesium iodide, lead iodide and lead bromide.
5. The method for preparing a perovskite thin film according to claim 1, characterized in that: The perovskite precursor solution containing small molecules is coated on the substrate by spin coating, spray coating, immersion coating and scraping coating.
6. A perovskite film, characterized in that: Prepared according to the method according to any one of claims 1 to 5.
7. A solar cell device, characterized in that: The invention comprises a substrate (1), a transparent electrode (2), an electron transport layer (3), a perovskite film layer (4), a hole transport layer (5) and a top electrode (6) which are stacked in sequence from bottom to top; the perovskite film (4) is prepared according to the method according to any one of claims 1 to 5, and the thickness of the perovskite film layer (4) is 300-600 nm.
8. The solar cell device according to claim 7, characterized in that: The transparent electrode (2) is made of an inorganic material or an organic conductive polymer. The inorganic material is indium tin oxide, zinc oxide or a metal oxide of tin oxide or a metal of gold, copper, silver or zinc; the organic conductive polymer is polythiophene, polyethylene sodium basic benzene sulfonate or polyaniline.
9. The solar cell device according to claim 7, characterized in that: The electron transport layer (3) is made of tin oxide, titanium oxide, zinc oxide, fullerene or a fullerene derivative.
10. The solar cell device according to claim 7, characterized in that: The hole transport layer (5) is made of nickel oxide, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly-3-hexylthiophene or poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].
Citation Information
Patent Citations
Bend-resistant perovskite solar cell and preparation method thereof
CN107611190A
Perovskite battery based on tungsten oxide and preparation method thereof
CN111261787A
Method for preparing perovskite solar cell by using anti-solvent containing ammonium acetate
CN114188487A
Ionic gel doped perovskite thin film and photoelectric device
CN115020591A